The effects of land use change on atmospheric nutrientdeposition in Central Sulawesi - Köhler, Stefan; Jungkunst, Hermann F.; Erasmi, Stefan; Gerold, Gerhard (ERDKUNDE, 2013)
Deposition rates in remote areas due to anthropogenic emissions are increasing in Asian countries and elsewhere. The burning of biomass in slash-and-burn activities, in addition to burning fossil fuel result in higher rates of atmospheric deposition at forest and agricultural sites. An investigation of bulk depositions in Central Sulawesi was conducted at 13 field sites along a land use cover gradient that included natural and unused sites, slash-and-burn sites, and consolidated agricultural systems around and in the Lore Lindu National Park, an area of more than 2310 km². Bulk depositions rates were measured with passive ion exchange collectors. Our results show that Central Sulawesi generally experiences low deposition rates. Depositions that originate mainly from anthropogenic sources, such as nitrate, are very low, i.e. between 0.1 and 0.8 kg ha-1 a-1, but increase to 2.4 nitrate kg ha-1 a-1 near slash-and-burn areas. Similar patterns were found for elements such as potassium and calcium. Indeterminate depositions were found for geogenic elements such as iron, manganese and aluminium and in some cases phosphorus. A principal component analysis allowed differentiation between the contributions of different sources and different element to the total deposition impact in most cases. Specific deposition rates were recorded for different land use systems. The main factor that generated different deposition patterns was biomass burning resulting from slash-and-burn activities. The latter determined the composition of atmospheric depositions of nearby sites, but the more distant sites inside the national park do not appear to be influenced by these anthropogenic activities yet.